Limitations of Criminal Punishment for Corruption Criminal Act Article 2 and Article 3 of the Corruption Criminal Act are Linked to the Supreme Court Regulation Number 1 of 2020 (Case Study of the high Court Decision Semarang Number 22/PID. TPK/2020/PT. SMG - Nirmansyah, Sandy; Wongso, Erni Suryani; Prayuti, Yuyut (Dinasti Research, 2025)
The issuance of Supreme Court Regulation Number 1 of 2020 concerning the Guidelines for Sentencing Article 2 and Article 3 of the Corruption Law, has given rise to pros and cons. The opposing opinion states that Article 2 and Article 3 of the Corruption Law, are sufficient to provide guidelines for sentencing so that there is no disparity in decisions, because both articles already regulate minimum and maximum sentences. The issuance of Perma No. 1 of 2020 is a form of intervention by the Supreme Court regarding the independence of judges in deciding a case. This is certainly contrary to Article 24 paragraph (1) of the 1945 Constitution. In addition, the issuance of Perma No. 1 of 2020 is also considered to have violated the principles in the formation of laws and regulations as regulated in Law Number 12 of 2011 concerning the Formation of Laws and Regulations. The decision of the Corruption Court which is the object of this research whose decision is guided by Perma No. 1 of 2020, such as the Decision of the Semarang District Court No. 41/Pid.Sus-Tpk/2020/PN.Smg, dated September 21, 2020, which has been canceled by the Semarang High Court Decision No. 22/Pid.Tpk/2020/PT.Smg, dated December 7, 2020, because the state losses have been recovered, so that the Bandung High Court decision has fulfilled substantive justice. In addition, the Formation of Perma No. 1 of 2020 is legally flawed because there is no higher statutory regulation order and it was not made based on the authority of the Supreme Court